TECHNOLOGICAL AND MANAGEMENT SOLUTIONS TO PREVENT EMERGENCIES AT OIL AND GAS FACILITIES - Teodoziїa YATSYSHYN; Lesya SHKITSA; Mikhaylo LYAKH; Vasyl-Danylo LIAKH (Carpathian Journal of Electrical Engineering, 2021)
Oil and gas production is accompanied by technological processes that can pose a significant threat to the environment. The analysis of conditions of occurrence of ecologically dangerous emergency situations in oil and gas production branch is presented. This became the basis for the formation of a technical solution to increase the environmental safety of hydrocarbon production processes. The system of diagnostics of the equipment for rejection of rods is improved. The main purpose of improving the rod magnetic flaw detector was to reduce emergencies with the rods of deep pumping units by rejecting the rods with defects. The improvement of the rod magnetic flaw detector was to reduce the scattering of the magnetic field in order to improve the quality of flaw detection. The use of this device will prevent accidents, which are accompanied by energy and resource costs, as well as causing environmental pollution by fluids. Based on the above research results the management model of environmental safety of oil and gas well is suggested.